2022
DOI: 10.1007/s00424-022-02671-1
|View full text |Cite
|
Sign up to set email alerts
|

Physiological relevance of proton-activated GPCRs

Abstract: The detection of H+ concentration variations in the extracellular milieu is accomplished by a series of specialized and non-specialized pH-sensing mechanisms. The proton-activated G protein–coupled receptors (GPCRs) GPR4 (Gpr4), TDAG8 (Gpr65), and OGR1 (Gpr68) form a subfamily of proteins capable of triggering intracellular signaling in response to alterations in extracellular pH around physiological values, i.e., in the range between pH 7.5 and 6.5. Expression of these receptors is widespread for GPR4 and OGR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 165 publications
(229 reference statements)
2
22
0
Order By: Relevance
“…OGR1 has been found in multiple tissues and functions as a proton sensor in a variety of circumstances. ( 16 , 17 ) We and others have previously demonstrated the presence of OGR1 in osteoblasts ( 8 , 18 , 19 ) and osteoclasts. ( 22 , 23 , 24 , 25 , 26 ) Our previous results in calvariae and primary osteoblasts from CD‐1 mice suggested that OGR1 in the osteoblast mediated the resorptive effect of MET.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…OGR1 has been found in multiple tissues and functions as a proton sensor in a variety of circumstances. ( 16 , 17 ) We and others have previously demonstrated the presence of OGR1 in osteoblasts ( 8 , 18 , 19 ) and osteoclasts. ( 22 , 23 , 24 , 25 , 26 ) Our previous results in calvariae and primary osteoblasts from CD‐1 mice suggested that OGR1 in the osteoblast mediated the resorptive effect of MET.…”
Section: Discussionmentioning
confidence: 90%
“…The ovarian cancer G protein‐coupled receptor (OGR1 or GPR68) senses extracellular protons (H + ) through its histidine residues and is coupled to Gq, which stimulates inositol phosphate (IP 3 ) production and subsequent mobilization of Ca i when activated by an increase in H + concentration. ( 16 , 17 ) OGR1 expression is upregulated in many neoplastic cells and may play a role in tumor biology ( 16 ) and is important in the response of bone to acidosis. ( 8 , 18 , 19 , 20 , 21 ) We and others have found that bone cells, including osteoblasts, ( 8 , 18 , 19 ) osteocytes, ( 18 ) and osteoclasts, ( 22 , 23 , 24 , 25 , 26 ) express OGR1.…”
Section: Introductionmentioning
confidence: 99%
“…[ 6,10 ] Immune cells can recognize and respond to extracellular H + through pH sensors on the cell surface. [ 167 ] For example, the pH‐sensing G protein‐coupled receptors are ubiquitously expressed by immune cells and can be activated by the protonation of several histidine residues of these receptors; [ 168 ] acid‐sensitive ion channels have been demonstrated to be expressed in monocytes, macrophages, and DCs and involved in acidosis‐mediated immune function impairment. [ 169 ] Overall, antitumor effector cells (such as T cells and NK cells) tend to lose function and undergo an anergic state followed by apoptosis when exposed to a low pH microenvironment.…”
Section: Combining Lactate Metabolic Regulation With Other Therapiesmentioning
confidence: 99%
“…They are ionic channels, enzymes, and G protein-coupled receptors (GPCRs). Some examples are TWIK-related acid-sensitive K + channel (TASK) [ 20 ], acid-sensing ion channels (ASICs) [ 24 ], insulin receptor–related receptor (IRRR) [ 34 ], soluble adenylyl cyclase (sAC) [ 98 ], ovarian cancer G protein-coupled receptor 1 (OGR1/ Gpr68 ), G protein-coupled receptor 4 (GPR4), and T cell death-associated gene 8 (TDAG8/ Gpr65 ) [ 57 ]. Moreover, an intracellular pH-senstive proline-rich tyrosine kinase 2 (PYK2) and a bicarbonate/CO 2 sensing protein receptor protein tyrosine phosphatase (RPTPgamma) have also been identified [ 15 , 69 ].…”
Section: Additional Mechanismsmentioning
confidence: 99%
“…The interaction between acid–base conditions and immune responses has been explored by research in several fields, such as oncology, pain and nociception, pulmonology, and gastroenterology, but it has been understudied by renal physiologists and nephrologists [ 31 , 56 , 57 , 91 , 143 ]. Acid–base conditions influence differentiation and motility of immune cells and their capacity to release substances [ 38 , 97 , 142 ].…”
Section: Additional Mechanismsmentioning
confidence: 99%